2016
DOI: 10.1021/acs.chemmater.6b03009
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Solid Polymethylaluminoxane: A Bifunctional Activator and Support for Slurry-Phase Ethylene Polymerization

Abstract: An insoluble form of methylaluminoxane, also known as solid polymethylaluminoxane (sMAO), has been synthesized by the controlled hydrolysis of trimethylaluminum (TMA) with benzoic acid, followed by thermolysis. Characterization of sMAO by multinuclear NMR spectroscopy in solution and the solid state reveals an aluminoxane structure that features "free" and bound TMA and incorporation of a benzoate residue. Total X-ray scattering (or pair distribution function, PDF) measurements on sMAO allow comparisons to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 39 publications
1
53
0
Order By: Relevance
“…Solid polymethylaluminoxane (sMAO) may be synthesized by the controlled hydrolysis of TMA with benzoic acid, 48 followed by two thermolysis steps (Scheme 3). We have reported that the ratio of these reactants is critical to the function of sMAO as an activating support, 43 with an [Al]:[O] ratio of 1.2 giving highest ethylene polymerization activity. Our starting point for the current study focussed on introducing C 6 F 5 OH as a modifier compound at different stages in this procedure.…”
Section: Synthetic Modification Of Solid Polyaluminoxanes (Smmaos)mentioning
confidence: 99%
See 1 more Smart Citation
“…Solid polymethylaluminoxane (sMAO) may be synthesized by the controlled hydrolysis of TMA with benzoic acid, 48 followed by two thermolysis steps (Scheme 3). We have reported that the ratio of these reactants is critical to the function of sMAO as an activating support, 43 with an [Al]:[O] ratio of 1.2 giving highest ethylene polymerization activity. Our starting point for the current study focussed on introducing C 6 F 5 OH as a modifier compound at different stages in this procedure.…”
Section: Synthetic Modification Of Solid Polyaluminoxanes (Smmaos)mentioning
confidence: 99%
“…The 27 Al Hahnecho 59 SSNMR spectra of sMMAO (0.10/B(C 6 F 5 ) 3 ) and (0.10/C 6 F 5 OH) at 15 kHz both show a broad envelope between 630 --715 ppm, which is very (b) (a) similar to that of the unmodified sMAO (Figures S12 and S17 in the Supporting Information). 43 Diffuse reflectance Fourier transform infrared (DRIFT) spectroscopy was employed to further characterize the structural properties of the active supports (Figures S18-S20 in the Supporting Information). The DRIFT spectrum of sMAO shows several bands between 2700-3100 cm −1 and ca.…”
Section: Scheme 4 Schematic Of the Synthesis Of B(c 6 F 5 ) 3 And C mentioning
confidence: 99%
“…Through baseline subtraction (or deconvolution) it is possible to determine both Me 3 Al and activator content by integration of these two signals with respect to the total integral due to MAO. The assumption used in our work is that the repeat unit of MAO is (Me 1.5 AlO 0.75 ).…”
Section: Resultsmentioning
confidence: 99%
“…This insoluble 'solid MAO' can act simultaneously as both co-catalyst and support in slurry phase ethylene polymerisation. 28,29 Results and discussion Synthesis of ( 3-R Ind # ) 2 ZrX 2 (R ¼ Me, Et or Ph; X¼ Cl, Br or CH 2 Ph)…”
Section: Introductionmentioning
confidence: 99%